2024
DOI: 10.1055/a-2274-0389
|View full text |Cite
|
Sign up to set email alerts
|

Blood Urea Nitrogen to Serum Albumin Ratio as A New Prognostic Indicator in Critically Ill Patients with Diabetic Ketoacidosis: A Retrospective Cohort Study

Tingting Hang,
Jing Huang,
Guiping He
et al.

Abstract: Purpose: Diabetic ketoacidosis (DKA) remains a life-threatening medical emergency. Blood urea nitrogen to serum albumin (BAR) demonstrated good predictive ability in the mortality of patients with various diseases. The study aimed to investigate the predictive value of BAR for in- and out-of-hospital mortality in critically ill patients with DKA. Methods: Data were obtained from the Medical Information Mart for Intensive Care III (MIMIC-III) database and all the eligible subjects were divided into two groups b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A previous study by Hang et al. demonstrated that elevated levels of BAR were associated with a higher risk of in-hospital mortality in critical DKA patients ( 25 ). Our study aimed to further investigate this relationship using a larger sample size and a multi-center approach.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study by Hang et al. demonstrated that elevated levels of BAR were associated with a higher risk of in-hospital mortality in critical DKA patients ( 25 ). Our study aimed to further investigate this relationship using a larger sample size and a multi-center approach.…”
Section: Discussionmentioning
confidence: 98%